Facilitating transition from maternity leave to work for working mothers: A self-efficacy intervention study - Akiko Kokubo; Katsuhiko Yoshikawa; Chia-Huei Wu (Cambridge Prisms: Global Mental Health, 2023)
The return from maternity leave to work is a critical career transition period for working mothers. To help their readaptation to work, we developed and examined a training program for cultivating their work–family balance self-efficacy in a pretest–posttest design and investigated the time-lagged effect of the boosted self-efficacy on their employment attitude and in-role performance after they returned to work. Data were collected from 100 maternity leave takers from 16 companies in Japan before the training (Time 1), immediately after it (Time 2) and 6 months after returning to work (Time 3), and from their supervisors at Time 3. We found that maternity leave takers displayed an increase in work–life balance self-efficacy after the training. We also found that work–life balance self-efficacy after the training (Time 2) predicted the participants’ in-role performance (Time 3) reported by their supervisors, but not employment attitude reported by the participants (Time 3). Our study thus offers preliminary evidence supporting the effectiveness of the training program in helping maternity leave takers’ readaptation to work, potentially supplementing existing family-friendly policies.